Work in uncertain and insecure times the changing employment relationship - Leighton, Patricia 1943-; McKeown, Tui (Routledge, 2020)
"With new technology, evolving business models and an increased diversity in working practices across organisations, we are facing changes to employment relationships on a scale that rival those of the so-called First Industrial Revolution. The changes are so dramatic, resulting not only in the need for workers to re-skill and adapt and for employers and policy-makers to rethink social protection provision, a complete reassessment of what we have come to know as traditional human resource management and employee relations is now required. In Change and Risk in Employment Relationships, the authors take a refreshing but realistic view of how contemporary work relationships are now organised and managed, and how these might evolve further in the future. Important questions that are addressed in the book include: 'who, precisely, is the employer?'; 'how do we now define a "career"?'; 'do we need to redefine or even discard ideas of "work engagement"?'; and 'what is now the psychological contract between employer and employee?'. Based on extensive research but written in an accessible and engaging style, each chapter in the book is clearly presented within a common framework, making it an ideal text to be used in the classroom and by practitioners alike. Elements include: the key issue; the regulations within different jurisdictions; interviews with key players and policy-makers; and a summary of what might come next. The book sets out how we might develop a fairer, robust and workable framework for the new economy"--